Strengthening Energy-Saving Culture Through the Implementation of State Defense - Dita Indra Febryanti; Syan Rosyid Adiwinata (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
The energy crisis results from imbalanced demand and availability. The Government commits to addressing future energy challenges in Indonesia through a conservation movement. Accelerating anticipatory measures with public support is crucial. Recognizing energy conservation as a societal responsibility, including students as agents of change, the implementation of a state defense program in higher education, is crucial. This research identifies students' energy conservation knowledge, analyzes dominant factors influencing its success, and assesses efforts to strengthen the conservation culture. Findings show awareness levels, with attitude toward belief as a primary hindrance. Combining technical and behavioral approaches is necessary for sustainable energy culture.